Study of phonological processes in prelingually deaf children with cochlear implants - Díaz Fresno, Estefania; Martínez López, Verónica; Núñez Batalla, Faustino (Revista de Investigación en Logopedia, 2024)
The main aim of the present study was to analyse and compare the frequency and nature of phonological processes in 19 cochlear-implanted prelingually deafened children between 3;0 and 4;6 years of hearing age with a group of 160 normal hearing children. A second aim was to determine whether the nature and frequency of phonological processes varied as a function of elicitation method in CI children. All participants were recorded in spontaneous conversation, which was transcribed and analysed using the CLAN software of the CHILDES Project. The phonological processes paradigm was adopted for the analysis, assessing development based on a phonological error rate calculated from the total number of processes produced and the tokens in spontaneous speech. In addition, CI participants were administered the Phonological Assessment of Child Speech Test. CI participants have a higher phonological error rate than their hearing age peers in all age groups, which would imply slower phonological development. In relation to the nature of the processes, they found more difficulties in processes that reduce the structural complexity of words followed by substitution processes. No significant differences were observed between the auditory age groups in the classes of processes according to the method of elicitation. Early diagnosis of deafness and the use of cochlear implants are emphasized for adequate phonological development.